Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1037/pas0000271
|View full text |Cite
|
Sign up to set email alerts
|

Determining appropriate screening tools and cut-points for cognitive impairment in an elderly Chinese sample.

Abstract: The establishment of normative data and screening cut-points for cognitive tasks is important to ensure the effective and timely detection of mild cognitive impairment (MCI) and Alzheimer's disease (AD). These need to be culturally relevant and account for known factors that impact on cognition such as age, education, and gender. In this study, 1,068 elderly Chinese residents of Shanghai completed a comprehensive series of cognitive tasks as part of a community screening study with 1027 meeting criteria for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 31 publications
(43 reference statements)
3
37
0
Order By: Relevance
“…Consistent with previous findings, older age was associated with lower scores [11][12][13][14][15][16][17][18][31][32][33][34][35]. We found a 1.0-point difference between the youngest (65-75) and oldest (75-85) groups; other studies have reported a difference of 0.6-2.4 points between similar age groups [13,[15][16][17]31].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with previous findings, older age was associated with lower scores [11][12][13][14][15][16][17][18][31][32][33][34][35]. We found a 1.0-point difference between the youngest (65-75) and oldest (75-85) groups; other studies have reported a difference of 0.6-2.4 points between similar age groups [13,[15][16][17]31].…”
Section: Discussionsupporting
confidence: 81%
“…We found a 1.0-point difference between the youngest (65-75) and oldest (75-85) groups; other studies have reported a difference of 0.6-2.4 points between similar age groups [13,[15][16][17]31]. Lower level of education was significantly associated with lower scores, correlating with results from other studies [11][12][13][14][15][16][17][18][31][32][33][34][35]. The difference in mean score was 1.4 points between the least and highest educated groups, in agreement with the original suggested method of adding an extra point for low education (≤12 years).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Some of the studies (23,24,35,36,39,(50)(51)(52)58) assessed the prevalence of MCI and AD ranging from 1.72% (58) to 32.9% (52) and 4.2% (35) to 9% (51), respectively. The number of adults with MCI ranged from 12 (58) to 2,049 (30) and the number of adults with AD ranged from 16 (51) to 1,061 (25). Mean age of the study participants ranged from 64.5 (40) to 82 years (50).…”
Section: Resultsmentioning
confidence: 99%
“…The MoCA is a cognitive battery that includes tests sensitive to executive functions and has higher sensitivity for diagnosing MCI (24,33,68). However, MoCA scores are strongly influenced by educational background as MoCA tasks are designed for a certain level of education making it difficult to assess individuals who are either illiterate or with low levels of education (30). Therefore, a MoCA basic version (MoCA-B) was developed to include tasks designed to assess the same cognitive domain regardless of the level of education (45,60,68).…”
Section: Discussionmentioning
confidence: 99%